2020
DOI: 10.3389/fmicb.2020.00461
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of High-Pressure Processing in Inactivation of the Hepatitis E Virus

Abstract: Hepatitis E virus (HEV) causes acute hepatitis with approximately 20 million cases per year globally. Based on genetic diversity, HEV is classified into different genotypes, with genotype 3 (HEV-3) being most prevalent in Europe and North America. The transmission of HEV-3 has been shown to be zoonotic and mainly associated with the consumption of raw or undercooked pork products. Herein, we investigated the efficacy of high-pressure processing (HPP) in inactivation of HEV-3 using a cell culture system. HPP ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…In a previous study [ 19 ], it was demonstrated that the cells of the A459 line infected with HEV and subjected to the pressure of 400 MPa applied for 1 min reduced the viral load of the virus by 2-log. Applying HPP to contaminated pâté protected it from HPP treatment [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study [ 19 ], it was demonstrated that the cells of the A459 line infected with HEV and subjected to the pressure of 400 MPa applied for 1 min reduced the viral load of the virus by 2-log. Applying HPP to contaminated pâté protected it from HPP treatment [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study [ 19 ], it was demonstrated that the cells of the A459 line infected with HEV and subjected to the pressure of 400 MPa applied for 1 min reduced the viral load of the virus by 2-log. Applying HPP to contaminated pâté protected it from HPP treatment [ 19 ]. The HPP inactivation of other foodborne viruses, including norovirus (HuNoV) [ 20 ] and hepatitis A (HAV), has been investigated [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies on the effect of HPP treatment on microorganisms in foods were conducted for bacteria, and fewer studies were established for foodborne viruses [12,43]. However, studies on the effect of HPP treatment on foodborne viruses in foods have increased in recent years [13][14][15][16][17][18]. The initial study of HPP treatment on viruses' sensitivity was conducted in 1929, by examining a non-enveloped plant virus, the tobacco mosaic virus (TMV) [44], while Basset et al [45] reported that a HPP treatment of 800 MPa for 45 min proved adequate for the inactivation of TMV.…”
Section: Foodborne Viruses' Inactivation By Hppmentioning
confidence: 99%
“…The infectious bursal disease virus (IBDV) during a HPP treatment of 600 MPa for 10-15 s at ambient temperature showed decreases of 5-6 log and 0.5-2 log in chicken meat homogenate and eggs, respectively [76]. Nasheri et al [15] reported that at HPP of 600 MPa for 5 min, HEV was decreased by 2 and 0.5 log in laboratory media and pork pâté, respectively, and concluded that HPP treatment may not be sufficient to mitigate the risk of HEV in pork pâté.…”
Section: Non-processing Parametersmentioning
confidence: 99%
See 1 more Smart Citation